Youth participatory research and evaluation to inform a Chagas disease prevention program in Ecuador. (August 2018) - Marco-Crespo, Belén; Casapulla, Sharon; Nieto-Sanchez, Claudia; Urrego, J. Guillermo Gómez; Grijalva, Mario J.
Highlights: By demystifying research practices youths can develop their reflexive and critical skills. Youth can explain cultural perceptions that can be key when developing health interventions. Developing effective youth leadership skills takes time and a longitudinal commitment. Youths as "lighthouses" that can peer train other youths and members of their communities. Abstract: This qualitative study engaged a group of young people in participatory research and evaluation activities in order to study to what extent engaging youth in health interventions can inform research and evaluation processes. We applied a youth participatory research and evaluation approach (PRE) to inform research and evaluation on the impact of a Chagas disease control program in southern Ecuador. Our main interest was to examine the methodological contributions of PRE to knowledge sharing for health intervention planning in the context of global health and neglected tropical diseases. The results of this study suggest that by demystifying research and evaluation practices and rendering them accessible and relevant, marginalized youth can develop critical and reflexive thinking skills that could be useful for decision-making on health promotion. Our findings also reveal the potential of youth as active participants in project development in ways that enhance, validate, and improve health interventions. Young people are interested in learning about and sharing local knowledge that can benefit research and evaluation processes. Despite the numerous strengths demonstrated by PRE, the inherent complexities of international development, such as cultural differences, asymmetrical power relations, and the ongoing challenges of sustainability, remain.